DEVELOPMENT OF IDEOLOGICAL POTENTIAL OF STUDENTS OF PEDAGOGICAL HIGHER EDUCATIONAL INSTITUTION ON THE BASIS OF NATIONAL AND SPIRITUAL VALUES (Archive of Conferences, 2020)
This article describes the role and importance of developing ideological and ideological potential of students of pedagogical higher educational institution on the basis of national and spiritual values.